SERUAN NABI IBRAHIM TERHADAP KAUMNYA DALAM MENANAMKAN AQIDAH TAUHID DALAM SURAT AL-AN’AM AYAT 74-79 - Ummu Safiah Binti Che Mat; APRYANTI APRYANTI (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2021)
This article shows the call of Prophet Ibrahim to his people in cultivating the belief of monotheism through natural phenomena found in Surat al-An‘am verses 74-79. This letter talks about the efforts of Prophet Ibrâhîm in inculcating the monotheistic beliefs of his father and his people who worshiped idols and worshiped the stars, moon and sun. Where what was conveyed by Prophet Ibrahim that is contained in his mind is a strong belief and trust from the guidance of Allah swt. The verse also tells about Prophet Ibrahim, where at that time Prophet Ibrahim made the stars, moon and sun as a medium to tell his people that the stars, moon and sun are God's creation and not the god they believe in. Prophet Ibrahim lived in an environment of worshipers of the stars, moons and stars. He educated his people by adapting and adapting to the level of understanding and knowledge so that his people believed in piety to the god of the universe, Allah swt. Then he accompanied his people towards true I'tikad step by step. That is why Prophet Ibrahim when he saw the star appear, Prophet Ibrahim said "this is my god." When the star sank Prophet Ibrahim said "I do not like something that is lost." When seeing the stars sink, so say against the emergence of the sinking of the moon and the sun. Prophet Ibrahim used the method of debate and argumentation with his people which aimed to break their misguided beliefs and lead to sound beliefs by thinking using logic with clear evidence. All the words of Prophet Ibrahim in the above verse describe his thought process to teach his people to find the One True God Allah swt.